Aged Opossums Show Alterations in Spatial Learning Behavior and Reduced Neurogenesis in the Dentate Gyrus - Tepper, Beata; Aniszewska, Agata; Bartkowska, Katarzyna; Grochocka, Lilianna; Turlejski, Krzysztof; Djavadian, Ruzanna (Frontiers in Neuroscience, 2019)
In many mammalian species including opossums, adult neurogenesis, the function of which is not completely understood, declines with aging. Aging also causes impairment of cognition. To understand whether new neurons contribute to learning and memory, we performed experiments on young and aged laboratory opossums, Monodelphis domestica, and examined the association between spatial memory using the Morris water maze test and the rate of adult neurogenesis in the dentate gyrus (DG). Modification of this test allowed us to assess how both young and aged opossums learn and remember the location of the platform in the water maze. We found that both young and aged opossums were motivated to perform this task. However, aged opossums needed more time to achieve the test than young opossums. Classical parameters measuring spatial learning in a water maze during a probe test showed that young opossums spent more time in the platform zone crossing it more often than aged opossums. Additionally, hippocampal neurogenesis was lower in the aged opossums than in the young animals but new neurons were still generated in the DG of aged opossums. Our data revealed individual differences in the levels of doublecortin in relation to memory performance across aged opossums. These differences were correlated with distinct behaviors, particularly, aged opossums with high levels of DCX achieved high performance levels in the water maze task. We, therefore suggest that new neurons in the DG of Monodelphis opossums contribute to learning and memory.